Physicochemical characterization of the BINA substation farm soils at Nalitabari, Sherpur (AEZ-22) - Khan, M R; Tarafder, M A; Arofi, S; Priti, M S; Hossain, M F (Bangladesh Journal of Nuclear Agriculture, 2025)
To investigate the physico-chemical characteristics of the farm of Bangladesh Institute of Nuclear Agriculture (BINA) at NalitabariSherpur farm soils, forty-four composite soil samples were collected and examined. The results on the distribution of soil particle sizes of the 44 soil samples, 14 had a sandy loam texture, 8 had a loam texture, 16 had a clay loam texture, 3 had a sandy clay loam texture, one had a silt loam texture, and one had a sandy clay texture. The soilranged from slightly acidic to moderately acidic. Nonetheless, the block's pH readings vary from 5.90 to 7.05 depending on its depth. Soil organic C contents ranged from 0.80 to 1.76%.The status of nutrient elements viz. N, P, K and S in most of the samples was very low or very low to medium. The total N concentration of 44 soil samples ranged from 0.019 to 0.10%. The soils' available P ranged from 5.20 to 19.40 ppm, the amount of accessible S varied from 10.72 to 22.86 ppm. The exchangeable potassium concentrations of the soils varied between 0.82 and 1.548 me%, In general, soils collected from BINA substation farm, Nalitabariwith varying depths have nearly identical exchangeable K contents. Considering the heavy metal the research areas' surface soil has a lower than allowed level of heavy metals. Therefore, these soils should be amended with organic matter for sustainable crop production. Bangladesh J. Nuclear Agric., 39(1): 87-99, 2025